Uso de microrganismos eficientes em mudas de chicória (Cichorium endivia L.) no município de Porto Grande/AP - (:unkn) unknown (Brasil, 2025)
Chicory (Cichorium endivia L.) is a widely cultivated leafy vegetable in Brazil, especially among family farmers, and holds economic and nutritional relevance, although its initial development may be limited by factors such as low-quality substrates, pathogens, and adverse environmental conditions. In this context, the use of Effective Microorganisms (EM) emerges as a sustainable alternative, as it consists of microbial consortia capable of promoting plant growth, improving soil conditions, and enhancing seedling vigor. This study aimed to identify, select, and evaluate the agronomic performance of EM isolated in the northern region of Amapá, applying them to the initial development of chicory seedlings in the municipality of Porto Grande/AP. The experiment was conducted in two stages: the first in the laboratory, focused on identifying and selecting microorganisms present in the field, and the second in a greenhouse, where the effect of liquid EM produced from solid material fermented for 30 days was tested. Microscopic analyses indicated the presence of the genera Aspergillus and Penicillium, characterized by white cottony and greenish-blue colonies, respectively, along with typical structural features confirming their morphological identity. In the greenhouse stage, a randomized block design was used, with four treatments and three replications: T1 – control; T2 – EM applied to seeds and soil; T3 – EM applied to seeds with an additional application at 7 days after sowing (DAS); and T4 – EM applied only at 10 DAS. Leaf area showed significant differences among treatments, with higher averages in T2 and T3. Shoot length was also superior under early application treatments, and the root system exhibited greater length and uniformity in T2 and T3, indicating enhanced nutrient absorption capacity. Therefore, the use of EM, especially through seed immersion in liquid EM and early applications prior to, improves essential morphological attributes for chicory seedling production, reducing losses and contributing to sustainable systems, especially in low-fertility Amazonian regions.
Use of efficient microorganisms in chicory seedlings (Cichorium endivia L.) in the Municipality of Porto Grande/AP
Keywords: Agricultura sustentável; mudas de hortaliças; biofertilizante; sustainable agriculture; vegetable seedlings; biofertilizer; Ciências agrárias; Agronomia